Relations of Human Epidermal Growth Factor Receptor 2 (HER2) Expression and E-Cadherin (CDH1) Expression in Breast Cancer Patients - Martga Bella Rahimi; Wirsma Arif Harahap; Yanwirasti Yanwirasti (Biomedika, 2021)
The aim of this study is to analyze the relations of Human Epidermal Growth Factor Receptor 2 (HER2) expression and E-Cadherin (CDH1) expression in breast cancer patients. To date, the synergistic effect of this CDH1/HER2 complex is not well clarified. The design of this study was cross-sectional with a total sample of 56 formalin-fixed paraffin tissue blocks that had been examined for HER2. Furthermore, CDHI expression was examined using the Immunohistochemistry staining technique with the Labeled Streptavidin Biotin Complex (LSAB) method. Bivariate analysis was performed using the Spearman correlation test with abnormally distributed data (p>0.05). Of the 56 data on breast cancer patients, most of the patients (87.5%) were diagnosed at the age of ≥40 years. The majority of cancer staging was IIIB, which was 42.9% of the total 56 patients. The study results shows that 80.0% of HER2-positive patients were in the strong CDH1 group. From these data, there is evidence of correlation between HER2 expression and CDH1 expression in breast cancer patients, however this correlation was not significant (p>0.05).